2013
DOI: 10.1007/8904_2013_236
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Oxidation Disorders in a Chinese Population in Taiwan

Abstract: Background: Fatty acid oxidation (FAO) disorders are a heterogeneous group of inborn errors in the transportation and oxidation of fatty acids. FAO disorders were thought to be very rare in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
1
23
1
2
Order By: Relevance
“…These data differ to those for the Chinese population: the c.985A>G mutation was not detected either in the present study or in another Chinese MCADD patient . Of the six mutations detected in the present study, however, a previously reported mutation in Chinese patients, that is, c.449_452del detected in patients 4, 5, and 6, occurred in 3/12 alleles in this study. This mutation is estimated to be relatively common in affected East Asian individuals, accounting for approximately 45% of mutant alleles in Japanese MCADD patients .…”
Section: Discussioncontrasting
confidence: 99%
“…These data differ to those for the Chinese population: the c.985A>G mutation was not detected either in the present study or in another Chinese MCADD patient . Of the six mutations detected in the present study, however, a previously reported mutation in Chinese patients, that is, c.449_452del detected in patients 4, 5, and 6, occurred in 3/12 alleles in this study. This mutation is estimated to be relatively common in affected East Asian individuals, accounting for approximately 45% of mutant alleles in Japanese MCADD patients .…”
Section: Discussioncontrasting
confidence: 99%
“…No clinical data, only the genotype, are available from the first case (Wang et al 2011). The second case was already symptomatic at the time of diagnosis through NBS (he presented with hyperammonemia and hypoglycemia after birth), and no further data about long-term outcome have been described (Chien et al 2013).…”
Section: Biochemical Findingsmentioning
confidence: 99%
“…To the best of our knowledge, until now, only two cases have been identified by positive expanded newborn screening (NBS) (Wang et al 2011;Chien et al 2013). No clinical data, only the genotype, are available from the first case (Wang et al 2011).…”
Section: Biochemical Findingsmentioning
confidence: 99%
“…6 The first variant (c.295C>T) promotes a substitution of arginine by cysteine in position 99 in exon 3, and this mutation has been previously described as pathogenic. 9 The second variant (c.1547T>C) is novel and leads to a substitution of phenylalanine by serine in position 516 in exon 12. This variant was not previously described, is not present in large population databases (EXAC, GNoMED, EVS), and is not reported in the disease databases (ClinVar and HGMD).…”
Section: Discussionmentioning
confidence: 99%